The concept of the notion “pupil’s success in the process of sports training” - Alexander D. Voronin (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The article analyzes the concepts of “success” and “professional success”, “success of sports activities”, “student’s success” which are studied in the framework of various theories: psychology, philosophy, theory of activity, pedagogy. In addition, the authors identified the fundamental approaches of organization of the training process of the student during his sports preparation for the formation of his success: self-centered, self-activity, anthropological, and also made their analysis and provided a description of each approach separately. In addition, based on studies of the concept of "success" from the point of view of various theories, the authors put forward the assumption that this concept is multifaceted. Furthermore, in this paper suggests that the problem of student’s success and ways of its formation in the sport training process is a very important social and psycho-pedagogical task in the field of amateur and professional sports. In addition, this article highlights the main components, revealing the concept of "success of the student in the process of sports training" in order to further build the model of formation of the success of students in sports activities: physiological, psychological, moral, technical and tactical, cognitive. At first the necessary condition here is the conceptual refinement of the concept of “success of the student in the process of sports training", which the author of the article suggests, based on an analysis of the above theories and empirical experience obtained during coaching and competitive activities. Due to the specification of the concept of "student’s success in the process of sports training", later on, based on this concept, the author plans to develop a number of pedagogical means of shaping the success of a student in the process of sport’s training.